The Influence Of Leadership, Work Environment On Work Spirit Of State Civil Apparatus In Sijunjung District - Ningsih, Kartika Shara; Syamsir, Syamsir (Universitas Dharma Wacana, 2023)
The botheration that occurs in government offices such as the Regional Planning and Development Agency, the Community Empowerment Service, and the Sijunjung Regency Kesbangpol is the abridgement of agent activity to assignment in accordance with the eyes and mission of Sijunjung Regency. In addition, the abridgement of acceptable administration from the administration makes the assignment ambiance bad for Sijunjung Regency employees. The purpose of this abstraction was to assay the aftereffect of the assignment ambiance on agent assurance in Sijunjung Regency, West Sumatra Province. This abstraction uses a quantitative approach. The abstraction citizenry consisted of 3,504 Accompaniment Civilian Apparatuses in Sijunjung Regency. The sample in this abstraction was bent through a stratified sampling address consisting of 104 respondents. Abstracts was calm through a check with a Likert Calibration altitude and analyzed application a simple Beeline Corruption Technique. The after-effects of this abstraction announce that there is a cogent access of the assignment ambiance on agent assurance in Sijunjung Regency.